Experimental investigation on the stability and abrasive action of cerium oxide nanoparticles dispersed diesel. (15th July 2017) - Balamurugan, S.; Sajith, V.
Abstract: Ceria nanoparticle is a well-known fuel borne additive for reducing the particulate emissions from diesel engines. Main challenges in the use of ceria nanoparticles are the lack of long-term dispersion stability in diesel and their effect on lubricity of diesel. The present work mainly focuses on synthesis of stable ceria nanoparticle diesel suspension and study on their lubricity. Ceria nanoparticles were synthesized by co-precipitation method and nano fluids were prepared by two-step method. The optimum concentration of oleic acid (surfactant) was determined based on critical micelle concentration studies and concentration of ceria nanoparticle in diesel was varied from 5 to 25 ppm. Long term dispersion stability studies using Dynamic light scattering system and Turbidity meter shows 10 ppm as an optimum concentration of ceria nanoparticle in diesel for maximum stability. Tribological properties of modified diesel were studied by a standard pin on disk apparatus. The wear rate was found to be reduced for all the nano additive concentrations in diesel and was least for 15 ppm. Based on studies conducted, 10 ppm is reported as an optimum concentration of nanoparticle in diesel having both enhanced stability and lubricity as compared to other concentrations of ceria nanoparticles in diesel. Highlights: Lack of dispersion stability of nanoparticles in diesel and their abrasive action are serious challenges. Synthesis of Ceria nanoparticle by precipitation method. Estimation of critical micelle concentration for the optimization of surfactant in diesel. Optimization of ceria nanoparticles in diesel based on stability and tribological studies. Use of 3D optical images for the investigation of tribology action of nanoparticles.